2017
DOI: 10.25061/2527-2675/rebram/2017.v20i1.379
|View full text |Cite
|
Sign up to set email alerts
|

Perfil Lípidico Dos Pacientes Hiv Positivos Em Uso Da Terapia Antirretroviral

Abstract: Corresponde a estudo descritivo de corte transversal, buscou-se evidenciar o impacto da TARV sobre o perfil lipídico. Realizada com 37 pacientes atendidos no ambulatório de Doenças Infecciosas e Parasitárias do centro de referência para HIV do Hospital Universitário Oswaldo Cruz em Recife-PE/Brasil. Através da realização de entrevistas, coleta de informações sobre terapia antirretroviral, curva de CD4 e carga viral obtidas nos prontuários. Tendo como aprovação no comitê de ética e pesquisa CAAE de nº 11365112.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Lichtenstein et al 46 studied a cohort of 1077 patients with a mean age of 41 years (85% men) and Segatto et al 42 evaluated 42 patients (55% men) and found an association between the higher levels of TCD4+ cells and lipodystrophy among individuals in treatment with ART. Therefore, this therapy tends to improve one's immune status, with a consequently slower progression of the disease and lower incidence of death, but is associated with the emergence of HIV-associated lipodystrophy 34,42,[47][48][49] .…”
Section: Discussionmentioning
confidence: 99%
“…Lichtenstein et al 46 studied a cohort of 1077 patients with a mean age of 41 years (85% men) and Segatto et al 42 evaluated 42 patients (55% men) and found an association between the higher levels of TCD4+ cells and lipodystrophy among individuals in treatment with ART. Therefore, this therapy tends to improve one's immune status, with a consequently slower progression of the disease and lower incidence of death, but is associated with the emergence of HIV-associated lipodystrophy 34,42,[47][48][49] .…”
Section: Discussionmentioning
confidence: 99%